The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.ces.2015.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular interactions control the shape of stains from drying droplets of complex fluids

Abstract: When a sessile droplet of a complex fluid dries, a stain forms on the solid surface. The structure and pattern of the stain can be used to detect the presence of a specific chemical compound in the sessile droplet. In the present work, we investigate what parameters of the stain or its formation can be used to characterize the specific interaction between an aqueous dispersion of beads and its receptor immobilized on the surface. We use the biotin-streptavidin system as an experimental model. Clear dissimilari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Hurth et al . 23 conducted evaporation of sessile droplet containing streptavidin- or biotin-coated fluorescent polystyrene (PS) particles and found that both the biological binding force and the capillary force play significant roles in particle deposition and that the viscous drag, van der Waals forces, and solid-solid friction forces are negligible. Recently, using particle tracking velocimetry technique, Yu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Hurth et al . 23 conducted evaporation of sessile droplet containing streptavidin- or biotin-coated fluorescent polystyrene (PS) particles and found that both the biological binding force and the capillary force play significant roles in particle deposition and that the viscous drag, van der Waals forces, and solid-solid friction forces are negligible. Recently, using particle tracking velocimetry technique, Yu et al .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, this knowledge base will help to explain deposit obtained from the drying of blood droplets which could be useful in forensics [45], biomarkers [46] and fingerprint residues in blood pattern analysis [6]. In biology, the bio-molecular interaction between the particles and substrate is important to understand the formation of bio-assays [47]. In this review, we tried to put recent studies that considered the effect of substrate heating, particle size and substrate wettability, however, the combined or coupled effect of each of these parameters over another for wider range is still lacking in the literature.…”
Section: Concluding Remarks and Future Outlookmentioning
confidence: 99%
“…In addition, other effects which were found significant in controlling the shape of the deposit are the particle shape, 6 surfactant concentration, 15 substrate elasticity, 16 ambient pressure, 17 particle size, 18 and bio-molecular interaction between the particles and the substrate. 19 In the context of evaporation on a hydrophobic surface, the direction of the characteristic evaporation-driven flow velocity inside the droplet on a superhydrophobic surface is opposite to that on a hydrophilic surface. The colloidal particles move upward due to a larger mass loss at the apex of the droplet as compared to near the contact line.…”
Section: ■ Introductionmentioning
confidence: 99%